2010
DOI: 10.1002/cncr.25287
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma in very young children

Abstract: BACKGROUND: This study was conducted to investigate presentation, treatment, and outcome in very young children with osteosarcoma. METHODS: The authors retrospectively analyzed the data of 2706 consecutive COSS patients with newly diagnosed osteosarcoma and identified 28 (1.0%) patients aged younger than 5 years at diagnosis. Demographic, diagnostic, tumor, treatment-related variables, response, and survival data were analyzed. RESULTS: Of the 28 preschoolers, 27 presented with high-grade central osteosarcoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 34 publications
(59 reference statements)
5
28
1
Order By: Relevance
“…1A-B The chemotherapeutic treatment guidelines for Ewing's sarcoma and osteosarcoma according to study proven protocols are shown. (A) The graph shows the chemotherapeutic protocols and major chemotherapeutic agents used for treatment of Ewing's sarcoma [3,7,15,31] and (B) osteosarcoma [3,6,15,21]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1A-B The chemotherapeutic treatment guidelines for Ewing's sarcoma and osteosarcoma according to study proven protocols are shown. (A) The graph shows the chemotherapeutic protocols and major chemotherapeutic agents used for treatment of Ewing's sarcoma [3,7,15,31] and (B) osteosarcoma [3,6,15,21]. …”
Section: Methodsmentioning
confidence: 99%
“…Both tumors affect the long bones of the appendicular skeleton and occur with occult metastases at the time of diagnosis in as much as 90% of cases [3]. Chemotherapy, following standardized study protocols [3,4,6,7,15,21,31], and potential radiotherapy (Ewing's sarcoma) in addition to wide resection have been seen to increase patients' survival [19]. Although the 5-year survival rate for patients with nonmetastasized Ewing's sarcoma has been less than 10% with resection only (with or without radiotherapy) [3], it has reached 50% to 75% with additional chemotherapeutic treatment [3].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable advances in the treatment of osteosarcoma have occurred, including the introduction of adjuvant chemotherapy and appropriate surgical excision (1)(2)(3)(4). However, there have also been advances in the field of immunotherapy for the treatment of osteosarcoma that have received less attention (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…This type of bone and soft tissue sarcoma predominantly affects children and young adults (1). Rapid advancements have occurred in the treatment of osteosarcoma, including the introduction of adjuvant chemotherapy, conformal radiotherapy and improved surgical excision (2)(3)(4)(5), and the 5-year survival rate in patients with localized disease is 50-70% (6). However, prognosis remains poor in relapsed disease and in patients that are resistant to the standard treatment modalities (7).…”
Section: Introductionmentioning
confidence: 99%